STRATEGI GURU PAI DALAM MENGATASI KESULITAN BELAJAR SISWA DI SDN SUNGAI PANDAN HULU KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - Yulinda Herawati; Barkatillah (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Teachers are one of the most important components in education who must be responsible for the implementation of the teaching and learning process. With these teacher roles and responsibilities, it is hoped that there will be no difficulties in learning. However, if difficulties occur in the learning process, it is hoped that a teacher will create good strategies so that the learning difficulties experienced by students can be resolved quickly and well. This research aims to find out how Islamic Education teachers' strategies are in overcoming learning difficulties among students at SDN Sungai Pandan Hulu, Sungai Pandan District, North Hulu Sungai Regency. The subject of the research was 1 PAI teacher who taught at SDN Sungai Pandan Hulu, Sungai Pandan District, North Hulu Sungai Regency. This type of research is qualitative. Data collection techniques are observation, interviews and documentation, then data processing is carried out through data reduction techniques, data display and data verification, then the data is analyzed using qualitative techniques using inductive methods. Based on the research results obtained, it can be concluded that the PAI teacher's strategy in overcoming students' learning difficulties at SDN Sungai Pandan Hulu, Sungai Pandan District, North Hulu Sungai Regency is: 1) Forms of student learning difficulties in PAI subjects at SDN Sungai Pandan Hulu, namely difficulty reading textbooks with students not being fluent in reading, difficulty recognizing the letters of the alphabet and understanding the contents of the reading in the book, reading hijaiyah letters with where a student does not know the hijaiyah letters, is lazy or has difficulty, 2) The PAI teacher's strategy in overcoming students' learning difficulties at SDN Sungai Pandan Hulu is an expository strategy that places the teacher as a processor of learning materials and provides examples of sentences in the book. Then the sentence is repeated with the students, if the students can and understand, they will be asked one by one, the meaning of which has been explained. Apart from that, the lecture method, question and answer method and demonstration method are also applied to make teaching easier for teachers.